PENGEMBANGAN BOOKLET CIRI DAN KLASIFIKASI MAKHLUK HIDUP SEBAGAI BAHAN AJAR IPA KELAS VII SMP NEGERI 4 RAMBAH - dahlia; Mubarrak Jismi; Rahayu Sefni; Brahmana Eti Meirina; Purnama Arief Anthonius (Fakultas Keguruan dan Ilmu Pendidikan Universitas Pasir Pengaraian, 2026)
This research aims to determine the suitability of a booklet on the characteristics and classification of living things as science teaching material. This research was carried out at SMP Negeri 4 Rambah in April-September 2023. This type of research is research and development of the modified Borg and Gall model. The research population and sample were all 20 class VII students of SMP Negeri 4 Rambah, Rambah District. The research sampling technique used was total sampling. Data were collected using non-tests in the form of questionnaires and data were analyzed descriptively. The results of the research show that the development of a science booklet on the characteristics and classification of living things for students at SMP Negeri 4 Rambah as a whole is included in the